Post-translational Modification Crosstalk and Hotspots in Sirtuin Interactors Implicated in Cardiovascular Diseases - Aggarwal, Suruchi; Banerjee, Sanjay K.; Talukdar, Narayan Chandra; Yadav, Amit Kumar (Frontiers in Genetics, 2020)
Sirtuins are protein deacetylases that play a protective role in cardiovascular diseases as well as many other diseases. Absence of sirtuins can lead to hyper-acetylation of both nuclear and mitochondrial proteins leading to metabolic dysregulation. The protein posttranslational modifications (PTMs) are known to crosstalk among each other to bring about complex phenotypic outcomes. Various PTM types like acetylation, ubiquitination and phosphorylation etc., drive transcriptional regulation and metabolism but such crosstalks are poorly understood. We integrated protein-protein interactions and PTMs from several databases to integrate information on 1251 sirtuin interacting proteins of which 544 are associated with cardiac diseases. Based on the 100,000 PTM sites obtained for sirtuin interactors, we observed that the frequency of PTM site (83 per protein) as well as PTM types (5 per protein) is higher than the global average for human proteome. We found that 60-70% PTM sites fall into ordered regions. About 83% of the sirtuin interactors contained at least one competitive crosstalk (in-situ) site with half of the sites occurring in CVD associated proteins. A large proportion of identified crosstalk sites were observed for acetylation and ubiquitination competition. We identified 614 proteins containing PTM hotspots (≥5 PTM sites) and 133 proteins containing crosstalk hotspots (≥ 3 crosstalk sites). We observed that a large proportion of disease associated sequence variants were found in PTM motifs of CVD proteins. We identified seven proteins (TP53, LMNA, MAPT, ATP2A2, NCL, APEX1 and HIST1H3A) containing disease associated variants in PTM and crosstalk hotspots. This is the first comprehensive bioinformatics analysis on sirtuin interactors with respect to PTMs and their crosstalks. This study forms a platform for generating interesting hypotheses that can be tested for a deeper mechanistic understanding gained or derived from big-data analytics.